About Functional Foods: The Probiotics and Prebiotics State of Art - Andrea Ballini; Ioannis Alexandros Charitos; Stefania Cantore; Skender Topi; Lucrezia Bottalico; Luigi Santacroce (MDPI AG, 2023)
Poor diet, obesity and a sedentary lifestyle have a significant impact on natural microbiota disorders; specifically, the intestinal one. This in turn can lead to a multitude of organ dysfunctions. The gut microbiota contains more than 500 species of bacteria and constitutes 95% of the total number of cells in the human body, thus contributing significantly to the host's resistance to infectious diseases. Nowadays, consumers have turned to purchased foods, especially those containing probiotic bacteria or prebiotics, that constitute some of the functional food market, which is constantly expanding. Indeed, there are many products available that incorporate probiotics, such as yogurt, cheese, juices, jams, cookies, salami sausages, mayonnaise, nutritional supplements, etc. The probiotics are microorganisms that, when taken in sufficient amounts, contribute positively to the health of the host and are the focus of interest for both scientific studies and commercial companies. Thus, in the last decade, the introduction of DNA sequencing technologies with subsequent bioinformatics processing contributes to the in-depth characterization of the vast biodiversity of the gut microbiota, their composition, their connection with the physiological function-known as homeostasis-of the human organism, and their involvement in several diseases. Therefore, in this study, we highlighted the extensive investigation of current scientific research for the association of those types of functional foods containing probiotics and prebiotics in the diet and the composition of the intestinal microbiota. As a result, this study can form the foundation for a new research path based on reliable data from the literature, acting a guide in the continuous effort to monitor the rapid developments in this field.